Metallographic display method for carbides in metallographic structure of high-temperature CrMo alloy heat-resistant steel

By using special metallographic corrosive agents and treatment methods, the problem of poor carbide display effect in high-temperature CrMo alloy steel in the prior art is solved, and the carbide morphology and distribution are clearly displayed, which improves the accuracy of tissue deterioration assessment. sex.

CN119322057APending Publication Date: 2025-01-17PETROCHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310875044.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing metallographic corrosion liquid has poor display effect on carbides in high-temperature CrMo alloy steels, and cannot fully and clearly display the morphology and distribution of carbides, resulting in increased difficulty or inaccurate evaluation of tissue deterioration.

Method used

Using metallographic corrosive agent made of a mixture of deionized water, concentrated hydrochloric acid and anhydrous ferric chloride, the volume ratio of deionized water to concentrated hydrochloric acid is 10:5 to 50:25, and the concentrated hydrochloric acid concentration is 36.0% to 38.0%. , after 30 minutes of stand, combined with polishing and grafting treatment, metallographic structure was observed by a microscope by hot air drying.

Benefits of technology

The display effect of carbide particles in CrMo heat-resistant high alloy steel is significantly improved, and the tissue morphology and distribution of carbides can be clearly displayed, providing an accurate basis for evaluating tissue deterioration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119322057A_ABST
    Figure CN119322057A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metallographic phase corrosion display methods, in particular to a metallographic phase display method for carbides in a metallographic structure of high-temperature CrMo alloy heat-resistant steel, which comprises the following steps: grinding and polishing the surface of a CrMo heat-resistant high alloy steel metallographic phase sample, then carrying out abrasion treatment by adopting a metallographic phase corrosive agent, washing and drying the CrMo heat-resistant high alloy steel sample after corrosion is completed, and finally obtaining the high-temperature CrMo alloy heat-resistant steel. And finally, observing the metallographic structure of the dried CrMo heat-resistant high alloy steel sample by using a metallographic microscope. According to the metallographic corrosive agent and the corrosion method, the structure form and distribution of carbides in the metallographic structure of the CrMo heat-resistant high-alloy steel can be effectively and clearly displayed, so that the aggregation and distribution conditions of the carbides in the crystal and the crystal boundary are judged, and a basis is provided for evaluating the structure deterioration of the CrMo heat-resistant high-alloy steel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallographic corrosion display methods, which is a metallographic display method for carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel, and also comprises a metallographic corrosive agent used for the metallographic display method for carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel. Background Art

[0002] Heat-resistant high-alloy steel has been widely used in large-scale petroleum and petrochemical plants in recent years because of its better resistance to high-temperature oxidation, resistance to hydrogen sulfide stress corrosion, and high thermal strength.

[0003] The basic organizational form of heat-resistant high-alloy steel is bainite or ferrite + bainite (pearlite may exist due to differences in heat treatment processes), often called bainitic steel. Due to the high service temperature of CrMo heat-resistant high-alloy steel and long-term operation in high-temperature environments, the carbides of bainite (pearlite) in the metallographic structure gradually disperse in spherical and large particles through atomic diffusion, and grow and aggregate over time to form strips and chains and aggregate at the grain boundaries, thereby reducing the bonding force of the grain boundaries and causing the high-temperature mechanical properties of the material to decrease, resulting in material performance degradation. Metallographic method is the most direct and effective non-destructive way to determine the degradation of material performance. How to clearly and perfectly display the morphology and distribution of carbides in steel through metallographic methods is one of the key factors affecting the degree of organizational degradation. Since the Cr element content in CrMo heat-resistant high-alloy steel is between low-alloy bainitic steel and high-alloy austenitic steel, its corrosion resistance is also between these two types of steel. Therefore, the commonly used low- and high-alloy steel metallographic etching liquid has insufficient corrosion ability or excessive corrosion, and thus cannot accurately display the carbide morphology.

[0004] At present, there is no specific metallographic etching solution for CrMo heat-resistant high alloy steel. For this type of bainitic steel, 4ml nitric acid + 100ml alcohol solution is often used to corrode its metallographic structure. Since the steel contains a high content of chromium, chromium reacts with nitric acid to form a passivation film, thereby preventing the nitric acid alcohol solution from chemically corroding the surface of the metallographic sample, resulting in the carbides in the metallographic structure not being fully displayed due to insufficient corrosion behavior (see Figure 1 ), the corrosion effect is unsatisfactory; due to the above reasons, the commonly used austenitic nickel steel and stainless steel corrosion liquid with strong corrosion ability: ferric chloride hydrochloric acid aqueous solution (5g ferric chloride + 50ml hydrochloric acid + 100ml water) is used to corrode the metallographic structure of CrMo heat-resistant high alloy steel. After corrosion, the carbides in the steel are still not completely clear. At the same time, because the corrosion liquid contains a lot of water, the carbides are mixed together by water stains during the corrosion process, resulting in the inability to clearly distinguish the size and distribution of carbides (see Figure 2 ), the corrosion effect is not ideal either.

[0005] In summary, the current on-site corrosion effect of commonly used low- and high-alloy steel metallographic etchants is not ideal, mainly because the distribution morphology of carbides cannot be fully and clearly displayed, and carbides are easily mixed with water stains and difficult to distinguish, which makes the assessment of organizational degradation more difficult or inaccurate. In order to observe the distribution of carbides at grain boundaries and within grains in steel, a metallographic etchant that can fully display the organizational morphology and distribution is needed. Summary of the invention

[0006] The present invention provides a metallographic display method for carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel, and also provides a metallographic etching agent used for the metallographic display method for carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel; the above-mentioned deficiencies of the prior art are overcome, and the present invention can effectively solve the problem that the existing metallographic display method has poor effects on the organizational morphology and distribution of carbides in high-alloy steel.

[0007] One of the technical solutions of the present invention is achieved by the following measures: a metallographic etchant is prepared by mixing deionized water, concentrated hydrochloric acid and anhydrous ferric chloride, the volume ratio of deionized water to concentrated hydrochloric acid is (10 to 50): (5 to 25), and 1g to 15g of anhydrous ferric chloride is added to every 5ml to 25ml of concentrated hydrochloric acid.

[0008] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions: The concentration of the above concentrated hydrochloric acid is 36.0% to 38.0%.

[0009] The deionized water may also be distilled water or other water with a purity level of Grade 2 or higher.

[0010] The prepared metallographic etching agent needs to be left to stand for 30 to 35 minutes.

[0011] The second technical solution of the present invention is achieved by the following measures: a method for metallographic display of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel using the metallographic corrosive agent described in one of the technical solutions, comprising the following steps: a first step, preparing a CrMo heat-resistant high-alloy steel metallographic sample according to a conventional metallographic sample preparation standard; a second step, grinding the surface of the CrMo heat-resistant high-alloy steel metallographic sample, and polishing the ground CrMo heat-resistant high-alloy steel sample using deionized water as a wetting agent; a third step, abrading the surface of the polished CrMo heat-resistant high-alloy steel sample using a metallographic corrosive agent, rinsing the surface of the CrMo heat-resistant high-alloy steel sample with anhydrous ethanol after the corrosion is completed, and then drying the surface of the CrMo heat-resistant high-alloy steel sample by hot air blowing; and finally observing the metallographic structure of the dried CrMo heat-resistant high-alloy steel sample using a metallographic microscope.

[0012] During the polishing process of metallographic samples (CrMo heat-resistant high-alloy steel metallographic specimens), deionized water is used instead of water polishing to remove impurities in the water remaining on the sample surface during the polishing process. At the same time, the configured metallographic etchant has strong corrosion resistance, which can greatly shorten the corrosion time and improve work efficiency. The metallographic structure analysis successfully shows that the carbide structure has increased from the previous 40% to 50% to 90% to 100%, thereby effectively improving the carbide particle morphology and distribution display effect of the CrMo heat-resistant high-alloy steel structure.

[0013] The following is a further optimization and / or improvement of the second technical solution of the above invention: In the second step, deionized water is used as a wetting agent and diamond metallographic polishing paste is used to polish the CrMo heat-resistant high-alloy steel sample.

[0014] The polishing time is 1 min to 3 min.

[0015] In the third step, the abrasion treatment time is 10s to 60s; before the abrasion treatment, the metallographic etchant is diluted with deionized water before use; when the surface of the CrMo heat-resistant high-alloy steel sample changes from mirror-like brightness to bright silver, the corrosion effect is best.

[0016] The corrosion of CrMo heat-resistant high-alloy steel by dilution wiping can control the corrosion effect and effectively prevent excessive corrosion of the sample while shortening the corrosion time.

[0017] The analytical purity of the above-mentioned anhydrous ethanol is ≥95%.

[0018] The drying time of the hot air blowing method is 2s to 30s.

[0019] The present invention can effectively and clearly display the organizational morphology and distribution of carbides in the metallographic structure of CrMo heat-resistant high-alloy steel by using the metallographic etching agent and the etching method, thereby judging the aggregation distribution of carbides in the grain and at the grain boundary, and providing a basis for evaluating the organizational degradation of CrMo heat-resistant high-alloy steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Attached Figure 1 This is the metallographic corrosion effect of 4ml nitric acid + 100ml alcohol solution on CrMo heat-resistant high alloy steel.

[0021] Attached Figure 2 The metallographic corrosion effect of 5g ferric chloride + 50ml hydrochloric acid + 100ml water on CrMo heat-resistant high alloy steel.

[0022] Attached Figure 3 This is the metallographic analysis diagram of the 1# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0023] Attached Figure 4 This is the metallographic analysis diagram of the 2# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0024] Attached Figure 5 This is the metallographic analysis diagram of the 3# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0025] Attached Figure 6 This is the metallographic analysis diagram of the 4# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0026] Attached Figure 7 This is the metallographic analysis diagram of the 5# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0027] Attached Figure 8 This is the metallographic analysis diagram of the 6# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0028] Attached Fig. 9 This is the metallographic analysis diagram of the 7# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0029] Attached Fig.10 This is the metallographic analysis diagram of the 8# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0030] Attached Fig.11 This is the metallographic analysis diagram of the 9# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0031] Attached Fig.12 This is the metallographic analysis diagram of the 10# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0032] Attached Fig.13 This is the metallographic analysis diagram of the 11# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0033] Attached Fig.14 This is the metallographic analysis diagram of the 12# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0034] Attached Fig.15 This is the metallographic analysis diagram of the 13# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel).

[0035] Attached Fig.16 This is the metallographic analysis diagram of the 14# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0036] Attached Fig.17 This is the metallographic analysis diagram of the 15# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0037] Attached Fig.18 This is the metallographic analysis diagram of the 16# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0038] Attached Fig.19 This is the metallographic analysis diagram of the 17# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0039] Attached Fig. 20 This is the metallographic analysis diagram of the 18# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0040] Attached Fig.21 This is the metallographic analysis diagram of the 19# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample.

[0041] Attached Fig. 22 This is the metallographic analysis diagram of the 20# delayed coking heating furnace tube (made of CrMo heat-resistant high alloy steel) sample. DETAILED DESCRIPTION

[0042] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions in which the solvent is water, for example, the hydrochloric acid solution is an aqueous hydrochloric acid solution.

[0043] Failure mechanism of heat-resistant high alloy steel: The operating temperature of CrMo heat-resistant high-alloy steel is about 600℃. If CrMo heat-resistant high-alloy steel operates at high temperature for a long time, the morphology and distribution of carbides in its metallographic structure will change, causing failure modes such as spheroidization and creep.

[0044] By using effective metallographic etching liquid and etching method, the organizational morphology and distribution of carbides in the metallographic structure of CrMo heat-resistant high-alloy steel can be effectively and clearly displayed, so as to judge the aggregation and distribution of carbides in the grain and grain boundary, and provide a basis for the evaluation of organizational degradation of CrMo heat-resistant high-alloy steel.

[0045] The present invention will be further described below in conjunction with embodiments: Example 1 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel comprises the following steps: a first step, preparing a CrMo heat-resistant high-alloy steel metallographic sample according to a conventional metallographic sample preparation standard; a second step, grinding the surface of the CrMo heat-resistant high-alloy steel metallographic sample, using deionized water as a wetting agent for the ground CrMo heat-resistant high-alloy steel sample, and using a diamond metallographic polishing paste to polish the CrMo heat-resistant high-alloy steel sample, and the polishing time is 1 minute; a third step, using a metallographic corrosive agent to abrade the surface of the polished CrMo heat-resistant high-alloy steel sample, and the abrasion treatment time is 10 seconds, when the surface of the CrMo heat-resistant high-alloy steel sample changes from mirror brightness to bright silver, the corrosion effect is optimal, and after the corrosion is completed, the surface of the CrMo heat-resistant high-alloy steel sample is rinsed with anhydrous ethanol, and then the surface of the CrMo heat-resistant high-alloy steel sample is dried for 5 seconds by hot air blowing; and finally, the metallographic structure of the dried CrMo heat-resistant high-alloy steel sample is observed with a metallographic microscope. The delayed coking heating furnace tube sample was processed according to the method described in this embodiment. The metallographic microscopic image thereof is shown in FIG. Figure 3 .

[0046] The metallographic etchant described in Example 1 is prepared as follows: 25 ml of deionized water is measured with a measuring cup; 12.5 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 2 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0047] The best corrosion time of the metallographic corrosive agent on the CrMo heat-resistant high-alloy steel sample is 15 (±5) seconds. When observed with the naked eye, the corrosion effect is best when the surface of the sample changes from mirror-like brightness to bright silver.

[0048] Example 2 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 15 seconds, and the hot air blowing method is used for drying for 10 seconds. The metallographic structure microscope image of this embodiment is shown in Figure 4 .

[0049] The metallographic etchant described in Example 2 is prepared as follows: 30 ml of deionized water is measured with a measuring cup; 10 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0050] Example 3 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 2 minutes; the rubbing treatment time of the third step is 11 seconds, and the hot air blowing method is used for drying for 7 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Figure 5 .

[0051] The metallographic etchant described in Example 3 is prepared as follows: 30 ml of deionized water is measured with a measuring cup; 10 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0052] Example 4 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the rubbing treatment time of the third step is 12 seconds, and the hot air blowing method is used for drying for 9 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Figure 6 .

[0053] The metallographic etchant described in Example 4 is prepared as follows: 30 ml of deionized water is measured with a measuring cup; 10 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0054] Example 5 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 13 seconds, and the hot air blowing method is used for drying for 12 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Figure 7 .

[0055] The metallographic etchant described in Example 5 is prepared as follows: 35 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 7 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0056] Example 6 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 14 seconds, and the hot air blowing method is used for drying for 15 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Figure 8 .

[0057] The metallographic etchant described in Example 6 is prepared as follows: 35 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 7 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0058] Example 7 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the abrasion treatment time of the third step is 14 seconds, and the hot air blowing method is used for drying for 20 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this example, and its metallographic microscopic image is shown in Fig. 9 .

[0059] The metallographic etchant described in Example 7 is prepared as follows: 35 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 7 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0060] Example 8 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 2 minutes; the rubbing treatment time of the third step is 15 seconds, and the hot air blowing method is used for drying for 25 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.10 .

[0061] The metallographic etchant described in Example 8 is prepared as follows: 25 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0062] Example 9 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 10 seconds, and the hot air blowing method is used for drying for 30 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.11 .

[0063] The metallographic etchant described in Example 9 is prepared as follows: 25 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0064] Example 10 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the rubbing treatment time of the third step is 20 seconds, and the hot air blowing method is used for drying for 5 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.12 .

[0065] The metallographic etchant described in Example 10 is prepared as follows: 25 ml of deionized water is measured with a measuring cup; 15 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0066] Embodiment 11 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 10 seconds, and the hot air blowing method is used for drying for 15 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.13 .

[0067] The metallographic etchant described in Example 11 is prepared as follows: 15 ml of deionized water is measured with a measuring cup; 14 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0068] Example 12 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the rubbing treatment time of the third step is 15 seconds, and the hot air blowing method is used for drying for 15 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.14 .

[0069] The metallographic etchant described in Example 12 is prepared as follows: 15 ml of deionized water is measured with a measuring cup; 14 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0070] Embodiment 13 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the abrasion treatment time of the third step is 12 seconds, and the hot air blowing method is used for drying for 17 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.15 .

[0071] The metallographic etchant described in Example 13 is prepared as follows: 18 ml of deionized water is measured with a measuring cup; 12 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0072] Embodiment 14 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the rubbing treatment time of the third step is 14 seconds, and the hot air blowing method is used for drying for 10 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.16 .

[0073] The metallographic etchant described in Example 14 is prepared as follows: 18 ml of deionized water is measured with a measuring cup; 12 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 5 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0074] Embodiment 15 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 15 seconds, and the hot air blowing method is used for drying for 20 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.17 .

[0075] The metallographic etchant described in Example 15 is prepared as follows: 20 ml of deionized water is measured with a measuring cup; 10 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0076] Example 16 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 2 minutes; the abrasion treatment time of the third step is 11 seconds, and the hot air blowing method is used for drying for 25 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.18 .

[0077] The metallographic etchant described in Example 16 is prepared as follows: 20 ml of deionized water is measured with a measuring cup; 10 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0078] Embodiment 17 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 12 seconds, and the hot air blowing method is used for drying for 10 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.19 .

[0079] The metallographic etchant described in Example 17 is prepared as follows: 15 ml of deionized water is measured with a measuring cup; 7 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 4 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0080] Embodiment 18 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the rubbing treatment time of the third step is 20 seconds, and the hot air blowing method is used for drying for 30 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig. 20 .

[0081] The metallographic etchant described in Example 18 is prepared as follows: 15 ml of deionized water is measured with a measuring cup; 7 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 4 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0082] Embodiment 19 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 3 minutes; the abrasion treatment time of the third step is 14 seconds, and the hot air blowing method is used for drying for 20 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig.21 .

[0083] The metallographic etchant described in Example 19 is prepared as follows: 20 ml of deionized water is measured with a measuring cup; 7 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0084] Embodiment 20 The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel is different from that of Example 1 in that the polishing time of the second step is 1 minute; the rubbing treatment time of the third step is 15 seconds, and the hot air blowing method is used for drying for 20 seconds. The delayed coking heating furnace tube sample is treated according to the method described in this embodiment, and its metallographic microscopic image is shown in Fig. 22 .

[0085] The metallographic etchant described in Example 20 is prepared as follows: 20 ml of deionized water is measured with a measuring cup; 7 ml of concentrated hydrochloric acid is measured with a pipette and added to the deionized water; 6 (±0.5) g of anhydrous ferric chloride is weighed with an electronic analytical balance and added to the hydrochloric acid aqueous solution, and stirred with a glass rod until the anhydrous ferric chloride is completely dissolved; after the preparation is completed, the prepared metallographic etchant is allowed to stand for 30 minutes before use. When using, take 2 ml of the prepared metallographic etchant, dilute it with 2 ml of deionized water, and perform abrasion treatment on the surface of the CrMo heat-resistant high-alloy steel sample.

[0086] Depend on Figures 3 to 22 It can be seen that the metallographic etching agent and method of the present invention can accurately and clearly display the carbide structure morphology and distribution in the metallographic structure of CrMo heat-resistant high-alloy steel.

[0087] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A metallographic etching agent, characterized in that It is prepared by mixing deionized water, concentrated hydrochloric acid and anhydrous ferric chloride. The volume ratio of deionized water to concentrated hydrochloric acid is (10 to 50): (5 to 25). 1g to 15g of anhydrous ferric chloride is added to every 5ml to 25ml of concentrated hydrochloric acid.

2. The metallographic etching agent according to claim 1, characterized in that The concentration of concentrated hydrochloric acid is 36.0% to 38.0%.

3. The metallographic etching agent according to claim 1 or 2, characterized in that Deionized water may also be distilled water or other water with a purity level of Grade 2 or higher; or / and, the prepared metallographic etching agent needs to be left to stand for 30 to 35 minutes.

4. A method for metallographic display of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel using the metallographic etching agent according to claim 1, 2 or 3, characterized in that The method comprises the following steps: a first step, preparing a CrMo heat-resistant high-alloy steel metallographic sample according to a conventional metallographic sample preparation standard; a second step, grinding the surface of the CrMo heat-resistant high-alloy steel metallographic sample, and polishing the ground CrMo heat-resistant high-alloy steel sample with deionized water as a wetting agent; a third step, abrading the surface of the polished CrMo heat-resistant high-alloy steel sample with a metallographic corrosive agent, rinsing the surface of the CrMo heat-resistant high-alloy steel sample with anhydrous ethanol after the corrosion is completed, and then drying the surface of the CrMo heat-resistant high-alloy steel sample by hot air blowing; and finally observing the metallographic structure of the dried CrMo heat-resistant high-alloy steel sample with a metallographic microscope.

5. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to claim 4, characterized in that In the second step, deionized water is used as a wetting agent and diamond metallographic polishing paste is used to polish the CrMo heat-resistant high alloy steel sample.

6. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to claim 5, characterized in that The polishing time is 1min to 3min.

7. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to claim 4, 5 or 6, characterized in that In the third step, the abrasion treatment time is 10s to 60s; or / and, before the abrasion treatment, the metallographic etchant is diluted with deionized water before use; or / and, when the surface of the CrMo heat-resistant high-alloy steel sample changes from mirror-like brightness to bright silver, the corrosion effect is best.

8. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to claim 4, 5 or 6, characterized in that The drying time is 2s to 30s when hot air blowing is adopted.

9. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to claim 7, characterized in that The drying time is 2s to 30s when hot air blowing is adopted.

10. The metallographic display method of carbides in the metallographic structure of high-temperature CrMo alloy heat-resistant steel according to any one of claims 4 to 9, characterized in that The analytical purity of anhydrous ethanol is ≥95%.